1994
DOI: 10.1183/09031936.94.07030472
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cotinine levels, household and personal smoking habit and season in 9-14 year old children

Abstract: The aim of this study was to determine the relationship of salivary cotinine levels with individual and household smoking habits and with the season in a sample (n = 146) of Italian schoolchildren aged 9-14 yrs. Active smoking and environmental tobacco smoke were measured by means of a confidential standardized interview with each participating child and by a self-reported questionnaire administered to the parents. Saliva samples were obtained twice: during winter from all children and during spring from a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 17 publications
1
24
1
Order By: Relevance
“…First, the cotinine level reflects exposure at a point in time. In this our study is like most other studies in the area, [13][14][15][16][17] which also use a single-point measurement of salivary cotinine. This method will still identify smokers with more than minimal ongoing exposure and be preferable to self-report given that subjects might misclassify their smoking status in studies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…First, the cotinine level reflects exposure at a point in time. In this our study is like most other studies in the area, [13][14][15][16][17] which also use a single-point measurement of salivary cotinine. This method will still identify smokers with more than minimal ongoing exposure and be preferable to self-report given that subjects might misclassify their smoking status in studies.…”
Section: Discussionmentioning
confidence: 88%
“…14 Reports have suggested that levels ranging from 1 to 2 ng/mL might be the result of passive smoking. [15][16][17] Levels in the range of 2 to 8 ng/mL were still considered passive smoking, given the reference levels in the literature.…”
Section: Salivary Cotinine Measurementsmentioning
confidence: 99%
“…43 This arrangement tends to minimize observed cotinine levels (because people spend more time indoors in extreme cold or hot weather than at other times, and ETS exposure is higher indoors than outdoors). 44 Another bias in our study that would tend to classify exposed children as unexposed and thus reduce the observed ORs is the cotinine level cutoff of 0.2 ng/mL used to define ETS exposure. This is a conservative definition of the upper limit of nonexposure as it represents a level that is well above the limit of detection with the technique used in NHANES III (0.05 ng/mL), and it corresponds to a medium low exposure level, slightly lower than the median cotinine level among nonusers of tobacco.…”
Section: Environmental Tobacco Smoke and Risk Of Cariesmentioning
confidence: 99%
“…Despite that the data procured were not substantiated by clinical procedures such as skin prick testing, exercise challenge and lung function tests, previous surveys have found that the ISAAC written questionnaire was reasonably sensitive and specific for bronchial hyperresponsiveness [12, 20]. Home ETS exposure was also assessed using questionnaire responses considering exposure status based on questionnaire responses which have been found to provide reasonably valid estimates of exposure in studies elsewhere [1,21,22,23]. The effects of potential confounders other than the exposures of interest were controlled in the multiple regression analysis using Poisson regression with a log-link function [17].…”
Section: Discussionmentioning
confidence: 99%